Kavânîn-i Âl-i Osmân der hulâsa-i mezâmîn-i defter-i dîvân ; Risâle-i vazîfe-hârân ve merâtib-i bendegân-ı Âl-i Osmân - Ayn Ali Efendi, 17. yy. ([İstanbul])
3 kitap 1 ciltte (1. kitap s. [2]-81 s., 2. kitap s. 82-118, [1] , 3. kitap s. [119]-140)